Григорій Сковорода у творчості Євгена Сверстюка - Рибка, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the problems of the Ukrainian literature history. The central aim of this work is to present a detailed analysis of the influence of Hryhory Skovoroda’s heritage on Evhen Sverstyuk. Evhen Sverstyuk’s esseys and letters are analyzed in the article. The author asserts that Evhen Sverstyuk researches Hryhory Skovoroda’s creativity in the deep connection with the heritage of M. Gogol, T. Shevchenko etc.